Compare the Effect of Addition of Low Dose Ketamine to Tramadol for the Prevention of Shivering Under Spinal Anesthesia - Abdul Sattar, Palvesha Amin, Tahmina Karim Bhatti, Aqeel Ahmad, Tayyab Ali, Abid Rafique Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To see if adding a mild dosage of ketamine to tramadol can help avoid shivering when under spinal anaesthesia. Study Design: Randomized study Place and Duration: The study was conducted at the department of Anesthesia, Sindh Government Liyari General Hospital Karachi and Shiekh Khalifa Bin Zayed Hospital, Quetta for the duration of six-months from December 2020 to May 2021. Methods: There were one hundred and seventy patients of both genders undergoing inguinal hernia were included in this study. Informed permission was obtained before to calculating demographic information such as age, sex and BMI. Patients were divided equally into two groups. Group A had 85 patients and received low dose ketamine 0.25 mg/kg (K) into tramadol and group B had 85 patients and received tramadol 0.5 mg/kg (T) alone. Post-treatment effectiveness among both groups was compared in terms of shivering control. We used SPSS 19.0 version to analyze complete data. Results: In group I the mean age of the patients was 33.9±9.76 years and mean age in group II was 31.5±3.23 years. There were 55 (64.7%) males and 30 (35.3%) females in group I while in group II 65 (70.6%) were males and 30 (29.4%) females. HTN and diabetes mellitus were the most common comorbidities found among both groups. 50 (58.2%) patients in group I had ASA class II and in group II 54 (63.2%) had ASA class II. We found that low dose ketamine to tramadol was effective in reduction of shivering in 33 (38.9%) as compared to tramadol alone shivering found in 41 (48.2%) cases. Conclusion: We concluded in this study that low dose ketamine into tramadol under spinal anesthesia is an effective and useful in terms of reduction in shivering as compared to tramadol alone in patients undergoing surgery.